Defense Policy: A Look at Bilateral Cooperation - M. Marzuq Ashidiqi; Rizky Dwi; Anom Wahyu Sasmita; Wawan Gunawan (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2024)
Indonesia's friendship with Russia has existed for more than seven decades. As a country with the second largest military force in the world, Russia has always been willing to assist Indonesia in realizing the country's defence and security. The article aims to review Indonesia's cooperative relationship with Russia, especially in defence. Using the literature study method, an understanding is produced that to realize the independence of defence equipment, the Indonesian government needs to increase defence cooperation with the Russian government. At least several reasons are behind it. First, historically, Indonesia's relationship with Russia has been very close. Russia positions Indonesia as a strategic partner. This condition allows Russia to not easily impose an embargo on weapons and weapon parts to Indonesia. Second, from an economic perspective, the price of weapons sold by Russia is relatively cheaper with the same quality and reliability, even more so than weapons from other country manufacturers. And third, there is a Russian commitment to transfer technology to support the independence of Indonesia's defence equipment